2020
DOI: 10.3389/fcell.2020.581340
|View full text |Cite
|
Sign up to set email alerts
|

Host Antiviral Response Suppresses Ciliogenesis and Motile Ciliary Functions in the Nasal Epithelium

Abstract: BackgroundRespiratory viral infections are one of the main drivers of development and exacerbation for chronic airway inflammatory diseases. Increased viral susceptibility and impaired mucociliary clearance are often associated with chronic airway inflammatory diseases and served as risk factors of exacerbations. However, the links between viral susceptibility, viral clearance, and impaired mucociliary functions are unclear. Therefore, the objective of this study is to provide the insights into the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…We attempted to investigate if any of the RV altered host genes would inhibit the replication of IAV. In our transcriptomic analysis, RV and IAV infection commonly upregulated genes related to innate sensing pathways, innate immune cytokine and chemokine signaling pathways, IFNs and antiviral signaling pathways, which agree with previous reports ( Bui et al., 2019 ; Murphy et al., 2020 ; Chen et al., 2020 ). Using a similar dual infection model, Manel Essaidi-Laziosi et al .…”
Section: Discussionsupporting
confidence: 93%
“…We attempted to investigate if any of the RV altered host genes would inhibit the replication of IAV. In our transcriptomic analysis, RV and IAV infection commonly upregulated genes related to innate sensing pathways, innate immune cytokine and chemokine signaling pathways, IFNs and antiviral signaling pathways, which agree with previous reports ( Bui et al., 2019 ; Murphy et al., 2020 ; Chen et al., 2020 ). Using a similar dual infection model, Manel Essaidi-Laziosi et al .…”
Section: Discussionsupporting
confidence: 93%
“…Functional pathway analysis revealed cilium function signature in asthmatic airway epithelial cells—out of the 12 downregulated genes, 8 were found to be similarly downregulated at 3 dpi in our study. Chen et al 27 stimulated differentiating hNECs by treatment with poly(I:C) to mimic RNA virus remnants, and found shortened and improper cilia formation in vitro. Similarly, clinical observations of reduced ciliogenesis and mucus hypersecretion have also been reported for chronic upper airway inflammatory diseases such as chronic rhinosinusitis with nasal polyps 17,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that abnormal ciliogenesis is associated with ultrastructural abnormalities in ciliated cells. 26 Thus, we further investigated the expression of motile cilia assembly markers, such as the outer dynein arm genes and radial spoke head genes. We found that the outer dynein arm heavy chain genes DNAH5, DNAH6, DNAH12 decreased significantly in both IR1 and IR5 groups.…”
Section: Resultsmentioning
confidence: 99%